Digital engagement: a preliminary analysis of marginalized youth in the information society - A. Rahim, Samsudin; Hasan, Hamisah (Universiti Putra Malaysia Press, 2017)
Efforts have been made to narrow the digital divide in disadvantaged communities through increased investment in Internet infrastructure, with such initiatives particularly advanced by community-based facilities. The hope is for such investment to afford more underprivileged groups the benefits of 21st century society, where many public services are, by default, accessible online. Accordingly, this study focusses on how 15-to-25-year-old Malaysian youths in marginalised communities engage with the Internet in performing various activities in their everyday lives. The findings indicate that the majority of these individuals have access to the Internet but that their engagement spans only basic activities such as communication and uploading and downloading of materials. In terms of intermediate and advanced activities, the investigated youths minimally shop online, search for educational materials and participate in civic and political causes. The results also indicate that attitudes towards the Internet considerably influence the decision of Malaysian youth to occupy themselves with digital activities. Fostering a digitally-inclusive society necessitates expanding digital engagement beyond basic activities - a goal that can be achieved by improving the digital literacy of youth and offering them participatory literacy programmes.